Workshop Pembuatan Kalkulator Akuntasi Berbasis Android Pada SMK PGRI Kota Pagaralam - Puspita, Desi; Arif, Alfis; Rahmadayanti, Fitria (FORDICATE, 2021)
The purpose of the implementation of community service activities is toprovide knowledge and basic skills in the field of application for accountingcalculator based on Android as supporting learning. The development ofinformation technology that supports the implementation of the activities(supporters) of the current work very much and offers facilities to their respectiveexcellence, the positive development of technology will make a good thing fortechnology users to facilitate daily activities. One technology that supports is asmartphone. Most students/I SMK PGRI City Pagar Alam already has a lot ofsmartphone based on Android. But here students/I SMK PGRI still not muchunderstand well in the use of Android learn especially the field of accounting.Method of implementation that is played in direct dedication come to the field toconvey the material through a workshop on making an Android-based accountingcalculator for students/I SMK PGR City Pagar Alam with the source of 1 personlecturer of Informatics Engineering Study Program and accompanied 1 studentsprogram Informatics Engineering STT Pagaralam. Conclusion in the report ofdevotion carried out in accordance with the prescribed procedures and cancontribute in the form of science to the students SMK PGRI and also can increasethe professionalism of lecturers in the Environment of Informatics EngineeringProgram of high School technology Pagar Alam. Results of the activities in SMKPGRI Siswa/I can increase knowledge and understanding especially the field oftechnology based on Android